2019
DOI: 10.1093/cdn/nzz050.or13-01-19
|View full text |Cite
|
Sign up to set email alerts
|

Commonly Applied Behavior Change Techniques Used in Complementary Feeding Programs in Low and Middle Income Countries: A Scoping Review (OR13-01-19)

Abstract: Objectives Suboptimal complementary feeding (CF) practices stunt child growth. Promotion of optimal CF can improve practices but little is known about how these interventions change behavior, limiting scalability. We conducted a systematic review of the literature for CF interventions in low/middle income countries and mapped behavior change techniques (BCT) using a previously validated method and taxonomy. Methods We searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This is similar to findings from a meta-analysis of intervention studies, which reported only 23% of included studies used a behaviour change theory (Davies et al, 2010). The lack of theories in the design of social and behavioural interventions has also been identified previously for breastfeeding (Bai et al, 2019;Wood et al, 2016) and complementary feeding (Pelto et al, 2016;Webb-Girard et al, 2019) interventions. In order to increase the likelihood for success, future interventions to engage family members should be designed based on appropriate theories and models that explain behaviour and systems.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is similar to findings from a meta-analysis of intervention studies, which reported only 23% of included studies used a behaviour change theory (Davies et al, 2010). The lack of theories in the design of social and behavioural interventions has also been identified previously for breastfeeding (Bai et al, 2019;Wood et al, 2016) and complementary feeding (Pelto et al, 2016;Webb-Girard et al, 2019) interventions. In order to increase the likelihood for success, future interventions to engage family members should be designed based on appropriate theories and models that explain behaviour and systems.…”
Section: Discussionsupporting
confidence: 86%
“…Programmatic learning from this review was limited by lack of detail and clarity on intervention design and delivery, particularly on engagement of family members. Lack of intervention detail is a common limitation reported by other reviews of nutrition interventions, and others have called for increased sharing of information about intervention design, theoretical basis, and implementation (Webb‐Girard et al, 2019 ). Future intervention studies should provide additional details about the intervention and describe standard intervention components such as using the Behavior Change Techniques (BCT) taxonomy (Michie et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation